Mandala Colouring Therapy And Cognitive Function In Elderly With Dementia - Noor Rochmah Ida Ayu TP; Reni Dwi Setyaningsih; Wilis Sukmaningtyas (Politeknik Kesehatan Makassar, 2019)
Dementia is a disorder of cognitive function in eldery. It is as one sign of an aging process, where there is a metabolic decline in the brain. Non-pharmacalogical theraphy with art theraphy, Mandala Therapy, believed to improved the cognitive function of older adult with dementia.This study aims to determain the effect of Mandala Therapy to improving cogntive function in elderly. Mandala Colouring Theraphy,which is expected to be able to help elderly to increase focus, concentration, reduce anxiety and can be an inherent process of meditation. The research design in this study used quasy experimental with the sample as 37 elderly. The measurement of cognitive function was carried out using the Mini Mental State Examination (MMSE) instrument which was carried out before and after the Mandala color therapy. The results found not significant difference between before and after Mandala colouring therapy (p = 0.324) with a mean decline of 0.69 points, but there were significant differences based on the severity of cognitive function disorders. Coloring therapy needs to be done routinely and continuously in order to provide meaningful results.